A complex of typical situations of the use of service weapons by police employees to reflect an armed attack - Chernykh V.V.; Fischer I.V. (Theory and Practice of Physical Culture, 2023)
The developed set of typical situations of using service weapons to repel an armed attack helps improve the level of professional preparedness of police officers.